Evaluating plasma biomarkers NfL, GFAP, GDF15, and FGF21 as indicators of disease severity in Charcot–Marie Tooth patients - Dace Pretkalnina; Dace Pretkalnina; Dace Pretkalnina; Elizabete Kenina; Elizabete Kenina; Linda Gailite; Dmitrijs Rots; Dmitrijs Rots; Kaj Blennow; Kaj Blennow; Henrik Zetterberg; Henrik Zetterberg; et al. (Frontiers in Neurology)
BackgroundCharcot–Marie–Tooth disease (CMT), a slowly advancing hereditary nerve disorder, presents a significant challenge in the medical field. Effective drugs for treatment are lacking, and we struggle to find sensitive markers to track the disease’s severity and progression. In this study, our objective was to investigate the levels of neurofilament light chain (NfL), glial fibrillary acid protein (GFAP), fibroblast growth factor 21 (FGF-21) and growth differentiation factor 15 (GDF-15) in individuals with CMT and to compare them to a control group. Our primary goal is to determine whether these biomarker levels are related to the severity of the disease.MethodsInitially, 44 patients with CMT and 44 controls participated in this study. CMT diagnosis was approved by genetic testing. Disease severity was assessed through clinical evaluations using the CMT Neuropathy Score version 2 (CMTNSv2). NfL and GFAP concentrations were measured using Single molecule array, while FGF-21 and GDF-15 concentrations were measured by enzyme-linked immunosorbent assays.ResultsIn the group of patients with CMT, the concentrations of GDF15, FGF21, NfL, and GFAP were significantly higher than in the control group (p < 0.05). NfL and GFAP levels were correlated with the CMTNSv2 score (rs = 0.46, p = 0.002; rs = 0.31, p = 0.04).ConclusionOur study has provided confirmation that plasma concentrations of NfL, GFAP, GDF15, and FGF21 are significantly elevated in patients with CMT compared to controls. Furthermore, NfL and GFAP levels were correlated with the clinical severity of CMT. These findings suggest that NfL and GFAP can be reliable disease indicators in future research.